Response surface methodology optimization for extraction of natural anthocyanins from Vietnamese Carissa carandas L. fruit - Pham, Tri Nhut; Xuan Huynh, Thi Ha; Tran, Thien Hien; Vo, Dai-Viet N.; Toan, Tran Quoc; Lam, Tri Duc; Le, Xuan Tien; Vu-Quang, Hieu (IOP Publishing, 2019)
Anthocyanins are naturally occurring compounds that are responsible for a wide variety of colors in many plants, fruits and vegetables. In this study, the extraction of natural anthocyanins from Vietnamese Carissa carandas L. beverage was optimized using response surface methodology (RSM). We applied a Box–Behnken design consisting of three levels and three factors. Examined factors are extraction temperature (ranging from 40 to 60°C), liquid to solid ratio (ranging from 2:1 to 4:1), extraction time (ranging from 30 to 60 min). Using 60% ethanol as solvent for the process, we determined the maximum yields of anthocyanin was 273.786 mg/L. This yield corresponds to extraction conditions of 3:1 (v/w) liquid to solid ratio, temperature of 48.10 °C with a 44.08 min extraction time. The experimental results also fit well with the proposed response model of anthocyanin yield (R2 = 0.9992). Therefore, this study suggested optimization of different extraction methods for the defatted fruit parts.